Torneamento da liga de alumínio da classe 6005 utilizando ferramenta cerâmica - Gorla, Frederico Ferreira Luiz [UNESP] (2015)
Machining processes are one of the most important manufacturing processes in the modern world. In these processes, there are many elements which will influence in the final result of the machined part. Among them, the tools are the principal factor of the rising cost, because its global influence on the process. In aeronautical industries, this can be more evidenced due the need to machining several alloys, between them, aluminum alloys. These alloys have to demonstrate a specific surface finishing to be used in aircraft's fuselage. This kind of industry is one of the segments which is still rising in Brazil, and they are looking viable alternatives in the manufacturing processes of materials, due the need to produce more and more parts and equipment, with costs increasingly reduced. The purpose of this project is the development of a ceramic with differentiated properties. The ceramics were developed using a pre-sintering at 1200 °C, with posterior sintering at 1600°C, and subjected to dry turning process on aluminum alloy 6005. The characterizations showed that ceramics presented with toughness on the center of 1700 MPa and on the surface of 1950 MPa, density 98,5 ±0,14. g/cm³. Ceramics were grinded and faceted, according to ISO standard 1832, and subjected to turning tests in a ROMI lathe brand, model GL240M, using cutting speeds of 500, 800 and 1000 m/min with different feed rates. The machining results showed low occurrence of flank wear to all cutting speeds, and better surface finishing average values of Ra = 0,4935 μm and Rt = 8,112 μm. In general, it could be seen that the tool presents important potential to machining 6005 alloy, and that the use of correct parameters can decrease and/or eliminate subsequent processes, providing important reductions in costs related to the machining processes